Odpowiedź :
4(2a-b)/3+ b/2=½(a-b) + 8 +2(a+b)/3
-1+3-b/4=a+⅓ /*4
8a-4b/3+b/2=½(a-b)+8+2a+2b/3 /*6
-4+12-b=4a+2
16a-8b+3b=3a-3b+48+12a+4b
4a-b+8-2=0
16a-5b-15a-b-48=0
4a-b+6=0
a-6b-48=0
4a-b+6=0/*-6
a-6b-48=0
-24a+6b-36=0
-23a-84=0
-23a=84/-23
a=-3,7
-6b=48+3,7
a=-3.7
-6b=51,7/-6
a=-3,7
b=-8,6
a=-3,7
-1+3-b/4=a+⅓ /*4
8a-4b/3+b/2=½(a-b)+8+2a+2b/3 /*6
-4+12-b=4a+2
16a-8b+3b=3a-3b+48+12a+4b
4a-b+8-2=0
16a-5b-15a-b-48=0
4a-b+6=0
a-6b-48=0
4a-b+6=0/*-6
a-6b-48=0
-24a+6b-36=0
-23a-84=0
-23a=84/-23
a=-3,7
-6b=48+3,7
a=-3.7
-6b=51,7/-6
a=-3,7
b=-8,6
a=-3,7